Influence of Obesity and Gender on the Postural Stability during Upright Stance - Cruz-Gómez, Nora S. (Obes Facts, 2011)
OBJECTIVE: To assess the influence of BMI group (lean/overweight/obese) and gender on the postural sway of adults and adolescents during quiet upright stance. METHODS: 90 women and 90 men, aged 12 to 67 years old, accepted to participate. The center of pressure during quiet upright stance was recorded using a force platform, during 4 conditions (eyes open/closed on hard/soft surface). Statistical analysis was performed using multivariate analysis of covariance. RESULTS: During recordings on hard surface, closing the eyes produced a larger increase of sway on obese subjects than on lean and overweight subjects, with a larger increase on the length and the area of sway. Although gender differences were found during the four sensory conditions, no interaction was observed between the BMI group and the gender. These results were not related to the age of the subjects. CONCLUSION: Compared to non-obese subjects, the postural stability of obese subjects may be more vulnerable when vision is not available, with no influence of the gender.